Studi Literatur: Metode Deteksi Pencemaran Mikroba pada Minuman Teh dalam Kemasan Standar ISO - Melda Mei Sari; Irdawati Irdawati (TSAQOFAH, 2026)
Packaged tea beverages are processed food products widely consumed by Indonesian society and are at risk of microbial contamination due to unhygienic production, packaging, or distribution processes. This literature review aims to identify and evaluate methods for detecting microbial contaminants in packaged tea beverages based on ISO standards. The methods reviewed include the Most Probable Number (MPN/APM) based on ISO 7251:2005, Total Plate Count (TPC) based on ISO 4833-1:2013, total coliform enumeration based on ISO 4831:2006, quantitative Polymerase Chain Reaction (qPCR) based on ISO/TS 12869:2012, Enzyme-Linked Immunosorbent Assay (ELISA) based on ISO 21569:2005, membrane filtration based on ISO 8199:2018, and mold and yeast enumeration based on ISO 21527-1:2008. The results of the review show that each method has different specificity, sensitivity, and applicability according to the type of microbial contaminant and the matrix characteristics of the tea beverage sample. The MPN and TPC methods remain the main choices in routine laboratory testing because they are relatively easy to apply and compatible with national regulations, particularly the Indonesian National Standard (SNI). Meanwhile, molecular methods such as qPCR offer advantages in terms of speed and specificity but require more advanced laboratory infrastructure support. The conclusion of this review affirms that the selection of microbial detection methods needs to consider the purpose of testing, the type of target microorganism, laboratory capacity, and conformity with ISO standards and national regulations. The implications of this review can serve as a reference in determining appropriate microbiological testing methods to support quality control and food safety in packaged tea beverage products.